Effectiveness of 7% versus 3% hypertonic saline nebulization in infants with acute bronchiolitis : A randomized controlled trail - Alok S Patil; Roopa M Bellad (Wolters Kluwer Medknow Publications, 2019)
Background and objective: Acute bronchiolitis, the most common lower respiratory tract infection,is the leading cause of hospitalization among infants. The objective of the study is to compare the effect of 7% hypertonic saline (HS) with 3% HS among infants with acute bronchiolitis. Methods: A total of 96 infants between the age group of 2 to 24 months with acute bronchiolitis and Bronchitis Severity Score (BSS)> 4 were included in this double-blinded, randomized controlled trial. The infants were grouped based on the therapy administered: group A (7% HS with L-adrenaline, n=48) and group B (3% HS with L-adrenaline, n=48).The prime outcome measure was Length of Hospital Stay (LHS). Whereas, the secondary outcome measures included BSS, heart rate, oxygen saturation, need and durationof supplemental oxygen, and adverse events. Statistical analysis was performed using SPSS 21 software. Results and Conclusion: Patient's baseline characteristics were alike in both the groups. The length of the hospital stay was 4.34 ± 1.01 days in 7% HS group and 4.59 ± 1.10 days in 3% HS group (P > 0.05). Treatment with 7% HS and 3% HS with adrenaline were associated with a decreased BSS and reduced length of hospital stay without any adverse effects among infants with acute bronchiolitis.